Synthesis, Characterization, Optical Transition and Dielectric Properties of the Schiff Base Ligand and Its Cobalt(II) and Palladium(II) Complexes - Buldurun, Kenan; Gündüz, Bayram; Turan, Nevin; Çolak N. (Springer New York LLC, 2019)
In this study, Co(II) and Pd(II) complexes of a Schiff base ligand, methyl-2-((5-bromo-2-hydroxybenzylidene)amino)-6-phenyl-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylate (L), were prepared and characterized used through FT-IR, UV–Vis., microanalyses, magnetic susceptibility, 1H-NMR, 13C-NMR, mass and thermogravimetric analyses. Optical transition and band structure properties, extinction characteristics, refractive indices and ambient behaviors, dielectric and electric susceptibility characteristics of the ligand, Co(II) and Pd(II) complex compounds were investigated in detail. Moreover, the impacts of the two complexes on these parameters and features of the ligand were examined. The main finding of the study was that the Co(II) complex decreased the optical band gap of the ligand from 2.682 to 2.357 eV. © 2019, The Minerals, Metals & Materials Society.
Keywords: Cobalt; dielectric and electric susceptibility properties; extinction characteristics; optical transition; palladium